2022
DOI: 10.32350/sir.62.03
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Chemistry of Flavonoids; their Biological and Therapeutic Potential

Abstract: Flavonoids are natural polyphenolic compounds, which are responsible for the taste and colors of medicinal plants, herbs, fruits, vegetables. Fruits (e.g., Berries, cherries, plums, apples, lemons, oranges, and grapes etc) and vegetables (e.g., broad beans, olives, onions, spinach, shallot etc) are the main sources of flavonoids. They also exist abundantly in cocoa products, black and green tea, red wine, red pepper, chamomile, celery, parsley, ginkgo, and mint. Flavonoids derivatives can also be synthesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They find important medicinal value due to their antioxidation, anticancer, anti-inflammation, antiobesity, antidiabetes, neuroprotective, antimutagenic properties, etc. 43 The reported literature also suggests that C. citratus is rich in TFC and TPC. 44 , 45 Their presence in A. indica has also been suggested in earlier studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They find important medicinal value due to their antioxidation, anticancer, anti-inflammation, antiobesity, antidiabetes, neuroprotective, antimutagenic properties, etc. 43 The reported literature also suggests that C. citratus is rich in TFC and TPC. 44 , 45 Their presence in A. indica has also been suggested in earlier studies.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are natural polyphenolic compounds that produce the color and taste in various parts of herbs, vegetables, plants, and fruits. They find important medicinal value due to their antioxidation, anticancer, anti-inflammation, antiobesity, antidiabetes, neuroprotective, antimutagenic properties, etc . The reported literature also suggests that C.…”
Section: Resultsmentioning
confidence: 99%
“…Plant materials show antioxidant activities due to the flavonoids [24,25] and phenolics content [26,27]. Flavonoids are responsible for the taste and color of plants, herbs, vegetables, and fruits [27].…”
Section: Resultsmentioning
confidence: 99%
“…Plant materials show antioxidant activities due to the flavonoids [24,25] and phenolics content [26,27]. Flavonoids are responsible for the taste and color of plants, herbs, vegetables, and fruits [27]. Flavonoids are compounds that have low molecular weight and are extracted from different parts of the plant.…”
Section: Resultsmentioning
confidence: 99%
“…Plant components used in traditional medicine exert their pharmaceutical effects through their ability to bind to plasma proteins. [45] Indeed, Liu et al 2008 reported that albumin has a high affinity for many flavonoids with hydrophobic interaction, which could explain the protective activity of polyphenols against thermal denaturation of albumin. [46] The denaturation of tissue-specific proteins is a crucial factor in the development of inflammatory and autoimmune disorders, such as arthritis.…”
Section: Determination Of Total Phenolic Total Flavonoids and Condens...mentioning
confidence: 99%